The effect of dehydration and irrigation on tendon adhesion formation after tendon exposure - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2012)
Objective: The aim of this study was to evaluate the effects of dehydration due to tendon exposure on adhesion formation on the tendon surface. Methods: Achilles tendons of 60 New Zealand white rabbits were surgically exposed and evaluated. In the control group (Group 1), the wound was closed immediately; and in the remaining two groups, Achilles tendons were exposed to air for 60 minutes without (Group 2) or with (Group 3) regular saline irrigation. After undergoing clinical examination, 50% of rabbits in each group were sacrificed 3 weeks postoperatively and 50% at the 6th postoperative week. Results: All tendons exposed to air exhibited mild or moderate degrees of adhesion. Compared to the control group, the incidence of adhesion formation was significantly higher in the groups where tendons had been exposed to air for 60 minutes, whereas no significant difference was found between the irrigated and non-irrigated groups. No limitations or contractures were detected in the hind limbs of the animals at the clinical examination. Conclusion: Regardless of irrigation, tendons are not prone to form clinically apparent adhesions during operations under 60 minutes of duration.
Keywords: Adhesion; air exposure; drying; irrigation; tendon; FLEXOR TENDONS; CHONDROITIN SULFATE; ARTICULAR-CARTILAGE; MOBILIZATION; RABBITS; MODEL; AIR